How can small satellites improve food security of equatorial countries and Singapore in a context of climate change? - Lim, Wen Xuan (Nanyang Technological University, 2024)
Amidst global challenges such as overpopulation and climate change, ensuring food security becomes paramount. Leveraging on satellite technology such as remote sensing imagery techniques, particularly small satellites like Cube Satellites, can offer innovative approaches for enhancing the resilience of food resources, due to their cost-effectiveness and ability to provide higher revisit times. Cube Satellites hold promising potential in applications like facilitating real-time monitoring of agriculture and aquaculture activities as well as early warning systems for climate-related disasters. This project utilises FreeFlyer software to simulate various satellite missions and perform mission analysis. Through literature review and the study of existing state-of-the-art satellite missions, this project was able to highlight the potential of Cube Satellites in improving the aquacultural aspect of food security via ocean colour monitoring applications. The proposed satellite mission concept and its coverage as well as its revisit times, involving a constellation of Cube Satellites, was investigated in a simulated scenario. The results indicate the feasibility of deploying a constellation of three Cube Satellites to augment coverage for equatorial countries and Singapore, complementing existing global satellite missions. This project ultimately shows that Cube Satellite missions are viable and scalable solutions that can address the evolving challenges in food security and informs the development and adoption of Cube Satellite usage in equatorial countries and Singapore.